2018
DOI: 10.3389/fnut.2018.00013
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and Potassium Intake from Food Diaries and 24-h Urine Collections from 7 Days in a Sample of Healthy Greek Adults

Abstract: ObjectiveThe main objective of the present study was to evaluate sodium and potassium intake, employing 24 h and spot urine samples and food diaries for seven consecutive days.MethodsFor seven consecutive days subjects recorded their food and drink intakes, and recorded and collected all urinations. Food sodium and potassium intake were analyzed in 24- and 6-h intervals from wake-up time. Urine indices were analyzed in first morning, 24- and 6-h intervals samples over the day from wake-up time. The study took … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
(53 reference statements)
3
11
0
Order By: Relevance
“…Examination of nationally representative data in 2011-2012 from NHANES revealed that only approximately 10% of US adults have a Na:K consistent with WHO guidelines and therefore may have reduced risk of CVD-related mortality [49]. The finding in this study that males had a higher potassium intake (via urinary excretion and dietary intake) compared to females is also similar to previous studies in Australia [48], US [50], UK [51], France [52] and Greece [43]. This disparity may be due to males consuming more overall energy per day.…”
Section: Na:ksupporting
confidence: 87%
See 1 more Smart Citation
“…Examination of nationally representative data in 2011-2012 from NHANES revealed that only approximately 10% of US adults have a Na:K consistent with WHO guidelines and therefore may have reduced risk of CVD-related mortality [49]. The finding in this study that males had a higher potassium intake (via urinary excretion and dietary intake) compared to females is also similar to previous studies in Australia [48], US [50], UK [51], France [52] and Greece [43]. This disparity may be due to males consuming more overall energy per day.…”
Section: Na:ksupporting
confidence: 87%
“…A recent systematic review and meta-analysis revealed the beneficial effect of increasing potassium to reduce blood pressure in adults, and an inverse relationship between potassium intake and risk of stroke in adults [10]. Potassium estimates were lower in the urinary excretion data compared to the 24-h diet recall data, which was expected [43] and likely reflects the non-urinary losses of potassium lost via the faeces [44]. It has been reported that most of ingested potassium is excreted in urine, however, 10-20% can be excreted in faeces and sweat [45,46].…”
Section: Potassiummentioning
confidence: 92%
“…Given that Greeks consume feta cheese almost on a daily basis, and that its consumption covers the largest part of total domestic consumption [1], feta, may consequently have a significant contribution on saturated fat and salt intake on the Greek population's diet, as this study showed. This is also supported by the study of Athanasatou et al [40], who reported that the main contributors to sodium intake in Greece are dairy products (including cheese, yogurt and milk), breads and snacks, in descending order.…”
Section: Discussionsupporting
confidence: 73%
“…Food sodium intake was low in both the food insecure group and control from the general population (1037.9 ± 509.3 versus 1245.29 ± 531.81 mg/day) compared to another study [29] of the Greek population reporting higher intakes (1983.2 ± 814.1 mg/day). This discrepancy could be linked to the fact that salt intake in this study did not include table salt or salt added while cooking, accounting for 10%-15% of salt intake [30][31][32]. At the same time the salt content of foods could also be underestimated, linked to the lack of updates of the Greek Food Composition Table [33].…”
Section: Discussionmentioning
confidence: 96%
“…The sustained high intake of meat products, confectionary and ice cream could also be a possible explanation for the high intake of SFA, which exceeded the 10% of energy cut off for both groups. Previous research has shown that such dietary habits are common among low socioeconomic status individuals and those receiving food assistance and could be linked with their purchasing power and the added cost of a 'healthy' diet [4,[29][30][31][32][33][34][35][36][37]. More specifically for the Mediterranean region, previous research [38,39] has indicated a link between the economic downturn and the decline of Mediterranean diet adherence within the general population, leading to inequities in food access.…”
Section: Discussionmentioning
confidence: 99%